Impact of biochar amendment on soil water soluble carbon in the context of extreme hydrological events. (October 2016) - Wang, Daoyuan; Griffin, Deirdre E.; Parikh, Sanjai J.; Scow, Kate M.
Abstract: Biochar amendments to soil have been promoted as a low cost carbon (C) sequestration strategy as well as a way to increase nutrient retention and remediate contaminants. If biochar is to become part of a long-term management strategy, it is important to consider its positive and negative impacts, and their trade-offs, on soil organic matter (SOM) and soluble C under different hydrological conditions such as prolonged drought or frequent wet-dry cycles. A 52-week incubation experiment measuring the influence of biochar on soil water soluble C under different soil moisture conditions (wet, dry, or wet-dry cycles) indicated that, in general, dry and wet-dry cycles increased water soluble C, and biochar addition further increased release of water soluble C from native SOM. Biochar amendment appeared to increase transformation of native SOM to water soluble C, based on specific ultraviolet absorption (SUVA) and C stable isotope composition; however, the increased amount of water soluble C from native SOM is less than 1% of total biochar C. The impacts of biochar on water soluble C need to be carefully considered when applying biochar to agricultural soil. Highlights: Biochar can release water soluble C and increase soil pH and ionic strength. Dry conditions and wet-dry cycles can increase soil water soluble C. Biochar can enhance water soluble C release from native soil organic matter under dry and wet-dry cycle conditions.